2022
DOI: 10.1063/5.0064234
|View full text |Cite
|
Sign up to set email alerts
|

Surface phonon polaritons for infrared optoelectronics

Abstract: In recent years, there has been significant fundamental research into surface phonon polaritons, owing to their ability to compress light to extremely small dimensions, low losses, and the ability to support anisotropic propagation. In this Perspective, after briefly reviewing the present state of mid-infrared optoelectronics, we will assess the potential of surface phonon polariton-based nanophotonics for infrared (3–100 μm) light sources, detectors, and modulators. These will operate in the Reststrahlen regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 202 publications
0
21
0
Order By: Relevance
“…To demonstrate this result we calculate the Purcell factor for the thin-nonlocal film system for a few dipole-film separations. We have previously demonstrated that decreasing the thickness of a nonlocal film leads to a spectral spreading of the longitudinal mode frequencies away from the zone-centre longitudinal phonon, in conjunction with an increase in the LTP coupling strength as a result of the enhanced electromagnetic fields at the film interfaces [16]. The results are shown in Fig.…”
Section: B Nonlocal Purcell Enhancementmentioning
confidence: 79%
See 3 more Smart Citations
“…To demonstrate this result we calculate the Purcell factor for the thin-nonlocal film system for a few dipole-film separations. We have previously demonstrated that decreasing the thickness of a nonlocal film leads to a spectral spreading of the longitudinal mode frequencies away from the zone-centre longitudinal phonon, in conjunction with an increase in the LTP coupling strength as a result of the enhanced electromagnetic fields at the film interfaces [16]. The results are shown in Fig.…”
Section: B Nonlocal Purcell Enhancementmentioning
confidence: 79%
“…The resulting excitations are hybrid modes termed longitudinal-transverse polaritons (LTPs), have a transverse electric field from their photonic component and a longitudinal one from the phonon field. This unique property has led to LTPs being proposed as a platform for mid-infrared optoelectronics as a result of the possibility of exciting them through longitudinal electrical currents, while still outcoupling to transverse free-space radiation in the far-field [16]. A recent series of publications has studied LTPs in more general systems, demonstrating them to be a general feature of polar resonators at the nanoscale [17][18][19] and a similar phenomenology has also recently been observed in a Yukawa fluid [20].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…4d). The available Q-factors are in the range of [15][16][17][18][19][20][21][22][23][24][25]) and ) respectively, which surpass that of graphene plasmon resonance in the THz regime 45 .…”
Section: Far-field Excitation Of Tunable Thz Hphps Using Periodic Tun...mentioning
confidence: 99%